2019
DOI: 10.1002/jcla.22902
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of droplet digital PCR and direct Sanger sequencing for the detection of the BRAFV600E mutation in papillary thyroid carcinoma

Abstract: BackgroundThe BRAF V600E mutation status is a useful diagnostic and prognostic marker for papillary thyroid carcinoma (PTC). Although it is a commonly used method, Sanger sequencing has several limitations in detecting the BRAF V600E mutation. The aim of this study was to evaluate the efficiency of droplet digital PCR (ddPCR) as an alternative method for the detection of the BRAF V600E mutation in PTC patients.MethodsSamples from a total of 120 patients with PTC and 30 patients with benign nodular thyroid dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…Also, it will be interesting to explore the association of BRAF/MIR17 signature with the most common BRAF V600E mutation by the newly emerged PCR techniques to add to its clinical utility. 49,50 Based on these limitations, future large-scale studies supported by functional in vitro and gene mutation exploring studies are warranted to confirm and validate the results.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it will be interesting to explore the association of BRAF/MIR17 signature with the most common BRAF V600E mutation by the newly emerged PCR techniques to add to its clinical utility. 49,50 Based on these limitations, future large-scale studies supported by functional in vitro and gene mutation exploring studies are warranted to confirm and validate the results.…”
Section: Discussionmentioning
confidence: 99%
“…By using highly sensitive methods, like ddPCR, we did not find a JAK2 V617F mutation in the control population, probably due to the low number of control samples used in our study. An increasing number of techniques have been developed for JAK2 V617F mutation identification by using molecular approaches including qPCR, such as high-resolution melt (HRM) [19], allele-specific oligonucleotide (ASO-PCR) [20], DNA direct sequencing [21], and recently ddPCR [22]. These techniques have different levels of LoD and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques have different levels of LoD and specificity. Direct sequencing has a reported LoD of approximately 15% mutant alleles [21], ASO-RT-PCR has a LoD of around 1% [22], while ASO-ddPCR and locked nucleic acid (LNA) RT-PCR have greater sensitivity for detecting rare mutations, with a limit of detection of about 0.1% [23][24][25]. Several studies have suggested that the JAK2 V617F mutational load correlates with disease course and could therefore be a predictive marker.…”
Section: Discussionmentioning
confidence: 99%
“…In routine molecular pathology laboratories, different molecular methodologies such as Sanger sequencing, allele‐specific PCR (AS‐PCR), droplet digital PCR (ddPCR) and polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) are employed for the detection of BRAF V600E mutation 7,15‐18 . Although different techniques have different performance rates and sensitivities, the technique performs to detect the mutation may have significant correlation with prevalance of BRAF V600E .…”
Section: Introductionmentioning
confidence: 99%